Multi-tissue metabolomic profiling reveals the crucial metabolites and pathways associated with scallop growth - Zhang, Yihan; Wang, Huizhen; Liu, Shiqi; Kong, Xiangfu; Chang, Lirong; Zhao, Liang; Bao, Zhenmin; Hu, Xiaoli (BMC genomics, 2024)
Bivalves represent a vital economic resource in aquaculture for their high productivity and extensive market demand. Growth is one of the most important and desired aquaculture traits for bivalves, regulated by multiple levels, notably intricate metabolic processes. However, the understanding of the metabolic profiles that influence bivalve growth is limited, particularly from a multi-tissue perspective. In this study, metabolic profiles of multiple tissues of Chlamys farreri with different growth performance were systematically investigated by ultraperformance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS). Through comparing the metabolic variation between fast-growing (FG) scallops and slow-growing (SG) scallops, 613, 509, 105, and 192 significantly different metabolites (SDMs) were identified in the mantle, gill, adductor muscle, and digestive gland, respectively. Growth-related metabolic pathways including sphingolipid metabolism, fatty acid biosynthesis, and ABC transporter pathway, along with 11 SDMs associated with growth traits were identified in all four tissues, implying they were involved in the growth of multiple tissues in scallops. Tissue-specific metabolic profiling indicated that sulfur-containing amino acid metabolism in the mantle potentially contributed to shell growth, while the gill synergistically participated with the mantle through various metabolic processes, such as tyrosine metabolism, glycine, serine, and threonine metabolism and melanogenesis; energy metabolism was crucial for adductor muscle growth; and nutrients digestion and absorption in the digestive gland were linked to scallop growth. Our results represent the first comprehensive analysis of the crucial pathways and metabolites associated with the growth of C. farreri, offering valuable insights for future bivalve aquaculture production.